Usage one of Reverse Engineering Application (Node.js Web) to Construct Software Engineering Documents - Edan, Naktal Moaid; Mahmood, Basim (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
In software engineering, documentation is considered the best way to distinguish the main functions of the software. The lack of software documentation may lead to consuming time and effort during the software design phase, which finally affects the quality of software. For instance, without proper documentation, the software maintainability index would never get a reasonable mark. The research has been progressive originally as a resilient concept, once the concept is proved to be developable in the Software Development Life Cycle (SDLC), the finishing product will be started to improve with satisfactory documentation. Also, software responsibility has caused complications, such as high costs of software repairs and inefficient process of knowledge transmission between developers. As a Software Reverse Engineering (SRE) method, this work uses a combination of an automatic class diagram creation tool with some manual tweaks, as well as source code analysis and comfortable interviews, to recover the product's design principles and requirement use cases. As a result, two documents will be produced: a Software Requirements Specification document and a Software Design Document